Halal digital entrepreneurship and disruptive technologies from the lenses of Maqasid al-Shari’ah - Elgharbawy, Amal A.M.; Azam, Md Siddique E; Muflih, Betania Kartika (Springer, 2023)
Digital entrepreneurship has become a popular field with the infusion of disruptive technologies, creating new opportunities for start-ups. However, the mechanism of start-ups’ disruptive innovation in the context of digital economy remains unclear. Halal digital entrepreneurship is a relatively new field that has not been fully explored, creating a gap in understanding the challenges and opportunities that halal digital entrepreneurs face in the context of disruptive technologies. The principles of Maqasid al-Shari’ah provide a framework for ethical and sustainable digital entrepreneurship that aligns with the values and principles of Islam. Nonetheless, their application to the context of halal digital entrepreneurship has not been fully explored. The intersection of halal digital entrepreneurship and disruptive technologies was the focus of a comprehensive literature review that placed an emphasis on Maqasid al-Shari’ah. The chapter is significant, providing an insight into halal digital entrepreneurship and disruptive technologies through the lens of Maqasid al-Shari’ah. The study also sheds light on the opportunities and threats that disruptive technologies present to halal digital entrepreneurs. The importance of Maqasid al-Shari’ah in guiding the creation of game-changing technologies for halal business owners is also emphasised in this chapter. Additionally, some successful examples of halal digital entrepreneurship have been demonstrated along with future research recommendations and prospects.